1972
DOI: 10.3171/jns.1972.37.2.0185
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotics with external ventriculostomies

Abstract: ✓ A review of 102 external ventriculostomies in 70 patients is reported. Forty-four patients received prophylatic antibiotics and 26 did not. The infection rate was significantly lower in the treated group, and the shunts could be left in place longer. Prophylactic antibiotics are advocated for patients in whom an external ventriculostomy is to be left in place for 3 days or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
4

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(57 citation statements)
references
References 0 publications
3
50
0
4
Order By: Relevance
“…A recent large review of 35 studies published from 1972 to 2013 noted that about half of these studies describe the use of periprocedural antimicrobial therapy [21], but did not assess the efficacy of this practice. Some studies also showed that use of prophylactic antimicrobials resulted in development of ventriculitis due to resistant organisms [162,167]. In one study, patients in the prophylactic antimicrobial arm developed ventriculitis caused by MRSA and Candida spp.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large review of 35 studies published from 1972 to 2013 noted that about half of these studies describe the use of periprocedural antimicrobial therapy [21], but did not assess the efficacy of this practice. Some studies also showed that use of prophylactic antimicrobials resulted in development of ventriculitis due to resistant organisms [162,167]. In one study, patients in the prophylactic antimicrobial arm developed ventriculitis caused by MRSA and Candida spp.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…The antimicrobial agent should be given before incision to achieve adequate tissue concentrations and should be continued for as long as 24 hours postoperatively, as studies included in these analyses generally administered therapy for this duration. With respect to CSF drain infection prevention, one review [20] that cited 10 studies addressed the use of prophylactic antimicrobials [47,68,[160][161][162][163][164][165][166][167]. One study with 102 ventriculostomies in 70 patients [165] included 44 patients who received antimicrobials and 26 who did not.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…8,15,17 All patients in our study received antibiotics at the time of insertion of their ventricular catheters. Yet, a positive CSF culture was found in an alarming 36.5% of patients as compared to 10% in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…30 In 1972, Wyler and Kelly presented a retrospective study of 70 patients with and without prophylaxis. 62 Infection rate in the prophylaxis group was 9%, compared with 27% without. Currently, there is no consensus on the use of prophylactic antibiotics.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%